Women’s femoral mass content correlates to muscle strength independently of lean body mass - Pimenta, Luciana Duarte (2019)
Introduction: There is limited consensus regarding the recommendation of the most effective form of exercise for bone integrity, despite the fact that weight training exercise promotes an increase in muscle mass and strength as recurrent responses. However, strength variations in women do not depend on muscle mass development as they do in men, but strength enhancement has shown the potential to alter bone mineral content (BMC) for both sexes. Objective: This study analyzed the potential of muscle strength, as well as that of whole-body and regional body composition, to associate femoral BMC in young women. Methods: Fifteen female college students (aged 24.9 ± 7.2 years) were assessed for regional and whole-body composition using dual-energy X-ray absorptiometry (DXA). Maximum muscle strength was assessed by the one-repetition maximum (1RM) test in the following exercises: bench press (BP), lat pulldown (LP), knee flexion (KF), knee extension (KE) and 45° leg press (45LP). Linear regression analyzed BMC relationships with regional composition and 1RM values. Dispersion and error measures (R2aj and SEE), were tested, defining p ≤0.05. Results: Among body composition variables, only total lean body mass was associated with femoral BMC values (R2aj = 0.37, SEE = 21.3 g). Regarding strength values, 1RM presented determination potential on femoral BMC in the CE exercise (R2aj = 0.46, SEE = 21.3 g). Conclusions: Muscle strength aptitude in exercises for femoral regions is relevant to the femoral mineralization status, having associative potential that is similar to and independent of whole-body lean mass. Therefore, training routines to increase muscle strength in the femoral region are recommended. In addition, increasing muscle strength in different parts of the body may augment bone remodeling stimulus, since it can effectively alter total whole-body lean mass. Level of Evidence II; Development of diagnostic criteria in consecutive patients (with universally applied reference ‘‘gold’’ standard).